2013
DOI: 10.1177/0954409713495017
|View full text |Cite
|
Sign up to set email alerts
|

New proposal for bogie-mounted sensors using energy harvesting and wireless communications

Abstract: The goal of the research presented in this paper is to design and incorporate new technologies into railway bogie-mounted sensors. It is often impossible to connect the mounted systems to physical wires due to their location in an inaccessible position or the distance to the energy source. Therefore, another power source must be used to solve this problem. Energy harvesting technology is an increasingly popular solution that extracts energy from the ambient environment and transforms it into electrical energy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…8 ), inertial-based vibration energy harvesting for railcar applications has only been explored in recent years. 9,10 De Pasquale et al. 9 designed an integrated electromagnetic system using a magnetic suspension energy harvester to generate electricity from freight train vibrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 ), inertial-based vibration energy harvesting for railcar applications has only been explored in recent years. 9,10 De Pasquale et al. 9 designed an integrated electromagnetic system using a magnetic suspension energy harvester to generate electricity from freight train vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…A design proposed by Ortiz et al. 10 for bogie-mounted sensors powered by a piezoelectric energy harvester was able to generate 6.1 mW of power from eight commercially available piezoelectric transducers.…”
Section: Introductionmentioning
confidence: 99%
“…Acceleration (g) 10 15 Although a number of studies have shown that energy from vibration can be harvested to power sensors and transmission modules, 10 inertial-based vibration energy harvesting for railcar application have only been explored in recent years. 11,12 For example an integrated electromagnetic system designed by Pasquale et al using magnetic suspension energy harvester was able to generate 100 mW from a freight train travelling at 80 km/h. 11 A design proposed by Ortiz et al for bogie mounted sensors powered by piezoelectric energy harvester was able to generate 6.1 mW from eight commercially available piezoelectric transducers.…”
Section: Introductionmentioning
confidence: 98%
“…11 A design proposed by Ortiz et al for bogie mounted sensors powered by piezoelectric energy harvester was able to generate 6.1 mW from eight commercially available piezoelectric transducers. 12 When designing an energy harvester for a heavy haul rail application, it is important to realize that the dominant frequency of the railcars can change significantly between the unloaded and loaded travel condition as a result of the added mass to the system. Base driven vibration energy harvesting devices produce maximum power when the resonant frequency of the generator matches the ambient frequency of the host structure.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have reported their application in freight cars. Ortiz et al [40] reported the most relevant work that experimentally observed the performance of piezoelectric vibration energy harvesting. It was found that such devices are suitable for monitoring the freight car bogies when associated with capacitors that can maintain the power supply for the wireless sensors.…”
Section: Introductionmentioning
confidence: 99%